Pengaruh inclusive leadership dan entrepreneurial leadership terhadap employee’s innovative behavior di perusahaan konstruksi - Soetedjo, Eric Himawan; Widoatmodjo, Sawidji (Universitas Tarumanagara, 2025)
The purpose of this study was to gain better understanding of how Inclusive Leadership and Entrepreneurial Leadership relates to Employee’s Innovative Behavior through Innovative Self-Efficacy. The primary data was collected with an online questionnaire and 111 respondents gave their responses. The data was then processed using Structural Equation Modeling - Partial Least Square (SEM-PLS) method using SmartPLS 4 software. The data was subjected to reliability and validity assessment, R-square and f-square assessments, as well as hypotheses testing. Through successive data-processing it was then discovered that contrary to prior researches, Inclusive Leadership does not affect Employee’s Innovative Behavior in a meaningful way, and Innovative Self-Efficacy does not mediate the aforementioned relationship. However, Entrepreneurial Leadership significantly affects Employee’s Innovative Behavior, confirming the findings of prior researches. Innovative Self-Efficacy plays a partial mediation role in the relationship between Entrepreneurial Leadership and Employee’s Innovative Behavior. Tujuan penelitian ini adalah untuk memahami bagaimana Inclusive Leadership dan Entrepreneurial Leadership berpengaruh terhadap Employee’s Innovative Behavior melalui Innovative Self-Efficacy. Data primer dikumpulkan dengan kuesioner online dan 111 responden mengirimkan jawaban. Data diproses dengan metode Structural Equation Modeling - Partial Least Square (SEM-PLS) menggunakan perangkat lunak SmartPLS 4. Data diuji reliabilitas dan validitasnya, diuji R-square dan f-square-nya, dan hipotesisnya diuji. Melalui pemrosesan data ditemukan bahwa berketerbalikan dengan penelitian sebelumnya, Inclusive Leadership tidak memengaruhi Employee’s Innovative Behavior secara berarti, dan lebih tidak berpengaruh melalui variabel mediasi Innovative Self-Efficacy. Akan tetapi, Entrepreneurial Leadership berpengaruh signifikan terhadap Employee’s Innovative Behavior, mengonfirmasi penemuan pada penelitian sebelumnya. Innovative Self-Efficacy melakukan peran mediasi parsial pada hubungan antara Entrepreneurial Leadership dan Employee’s Innovative Behavior.